Approximation of classes of periodic functions with small smoothness - Bushev, D. M. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove that the approximations of classes of periodic functions with small smoothness in the metrics of the spaces C and L by different linear summation methods for Fourier series are asymptotically equal to the least upper bounds of the best approximations of these classes by trigonometric polynomials of degree not higher than (n - 1). We establish that the Fejér method is asymptotically the best among all positive linear approximation methods for these classes.